2012
DOI: 10.1161/atvbaha.112.247890
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Effects of Peroxisome Proliferator-Activated Receptor-Δ Agonist GW501516 in Subjects With Low High-Density Lipoprotein Cholesterol

Abstract: Objective-Peroxisome proliferator-activated receptor-δ-induced upregulation in skeletal muscle fatty acid oxidation would predict the modulation of lipid/lipoproteins. Methods and Results-GW501516 (2.5, 5.0, or 10.0 mg) or placebo was given for 12 weeks to patients (n=268) with high-density lipoprotein (HDL) cholesterol <1.16 mmol/L. Fasting lipids/apolipoproteins (apos), insulin, glucose, and free fatty acid were measured; changes from baseline were calculated and assessed. A second smaller exploratory study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 21 publications
1
48
0
2
Order By: Relevance
“…4 In healthy humans, a synthetic PPARδ agonist, GW501516, reduced postprandial plasma triglycerides, increased high-density lipoprotein, and increased muscle expression of enzymes involved in fatty acid oxidation. 5 Similar effects were observed when PPARδ was activated in obese individuals, 6,7 people with low high-density lipoprotein, 8 and those with elevated low-density lipoprotein on statin therapy. 9 PPARδ is also known to affect macrophage biology because its deletion in this cell type disrupts phagocytosis 10 and promotes insulin resistance in addition to impairing the M1 (more inflammatory) to M2 (more inflammation resolution) transition.…”
Section: See Accompanying Article On Page 52mentioning
confidence: 70%
“…4 In healthy humans, a synthetic PPARδ agonist, GW501516, reduced postprandial plasma triglycerides, increased high-density lipoprotein, and increased muscle expression of enzymes involved in fatty acid oxidation. 5 Similar effects were observed when PPARδ was activated in obese individuals, 6,7 people with low high-density lipoprotein, 8 and those with elevated low-density lipoprotein on statin therapy. 9 PPARδ is also known to affect macrophage biology because its deletion in this cell type disrupts phagocytosis 10 and promotes insulin resistance in addition to impairing the M1 (more inflammatory) to M2 (more inflammation resolution) transition.…”
Section: See Accompanying Article On Page 52mentioning
confidence: 70%
“…Hansen et al (2011) and Olson et al (2012) have already found that a dual PPARa/g agonist, aleglitazar, and GW501516, a PPARd agonist, can significantly decrease LDL-C levels in humans, which suggested a potential LDL-lowering effect triggered by activating different isoforms of PPARs. The mechanism of increased removal of LDL particles could be possibly attributed to the formation of LDL with a higher affinity for the LDL receptor, followed by a more rapid catabolic rate when PPARa agonist, such as fibrate, was used for treatment (Staels et al, 1998), whereas a possible mechanism for PPARd could be due to the reduction of the Niemann-Pick C1-like 1 (NPC1L1) protein by PPARd activation in the intestine as the inhibition of NPC1L1 would lead to reduced cholesterol absorption (Riserus et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, treatment with GW501516 results in improved circulating apolipoproteins, LDL and HDL cholesterol and hepatosteatosis (51) . Finally, administration of MBX-8025 to moderately obese subjects improves circulating lipid and cholesterol profiles (52) .…”
Section: Drugs Mimicking Exercisementioning
confidence: 99%